Pengaruh Strategi Inovasi Terhadap Kinerja Bisnis Dengan Literasi Keuangan Sebagai Variabel Intervening Pada Ukm Tas dan Koper Tanggulangin Sidoarjo - Monika Dyah Novy Larashati; Hariyati Hariyati (Jurnal Akuntansi, 2021)
This study aims to analyze the relationship of innovation strategies on business performance with financial literacy as an intervening variable in bag and luggage SMEs in Sidoarjo Tanggulangin. The independent variable used in this study is an innovation strategy with product innovation and process innovation. This study uses a purposed sampling method with a total sample of 100 bag and luggage craftsman SMEs in Sidoarjo Tanggulangin. The analytical method used is a questionnaire with a validity and reliability test and multiple linear regression analysis.The results of this study indicate that innovation strategies affect business performance, and financial literacy. Financial literacy affects business performance, but financial literacy cannot interfere with the relationship betweeninnovation strategy and business performance.